“It feels like I have a camera in my eye”: New methods for literacies research in maker-oriented classrooms - Hughes, Janette; Morrison, Laura; Robb, Jennifer A.; Hagerman, Michelle Schira (Frontiers in Education, 2023)
This paper focuses on new data collection methods made possible through first-person-perspective or point-of-view (POV) recording technology and how these tools can provide important insights into students’ digital making and learning processes. Our study specifically used “spyglasses”, which look and feel like regular glasses that one would wear to improve their vision. They are equipped with an integrated video camera and recording functionality. The findings indicate that using tools that allow data to be collected from the student perspective gives access to important, alternate narratives about what students’ final products might show or represent about their digital skills and competencies. Our findings also explore the important technical, ethical and data management considerations associated with using spyglasses as a data collection tool. Future research could explore the gap between researcher interpretation of collected data when it is not ‘read’ alongside, or compared against, documentation from the ‘insider’ perspective.